Cuantificación y caracterización de agua y efluentes en establecimientos lecheros I. Demanda de agua y manejo de efluentes - Nosetti, L. (2002)
This study was carried out to quantify and characterize water demands in the different stages of the milking process and effluent management, in order to establish management criteria in dairy farms in Buenos Aires. Sixty-five dairy farms in three dairy areas were selected, and their farmers were surveyed. Water volumes used during the different milking routines were quantified in six of them, these will later become part of the total effluent. Surveys showed the several destinations of effluent generated during the milking process. Some, like effluent discharge into water bodies, may result in their contamination. Others, such as poorly designed effluent storages, could be responsible for the leaching of pollutants into groundwater. It was established that 74,47 to 91,29% of the total water volume was used by the plate-cooler operation (4,65?9,20 L.water/L.milk). Groundwater used by the plate-cooler can be reused, as its quality is not affected. This characterization allows to adequate and diminish water volumes used in dairy farms, giving priority to those practices that represent the largest water demands. The rational water use and effluent management will allow to minimize the potential environmental impact from one of the most important livestock productions in this region.